1999
DOI: 10.1007/bf02432795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of He-Ne laser radiation on lipids in platelets

Abstract: Low-intensity He-Ne laser radiation induces metabolic rearrangements in platelet lipids and activates some lipid-dependent systems of cell regulation as well as the synthesis of lipidlike second messengers. Modification of the lipid phase and physicochemical state of biological membranes are the molecular basis of biochemical adaptation of the platelets to laser radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Charge modification results in changes in the entire structure of the cell membrane. R/NIR leads to conformational changes in membrane proteins or transport 45 , resulting in the activation of a cellular system, and the synthesis of the secondary messengers 47 . Such assumptions indicate that the cell membrane structure is involved in the modification of PLT activity by light.…”
Section: Discussionmentioning
confidence: 99%
“…Charge modification results in changes in the entire structure of the cell membrane. R/NIR leads to conformational changes in membrane proteins or transport 45 , resulting in the activation of a cellular system, and the synthesis of the secondary messengers 47 . Such assumptions indicate that the cell membrane structure is involved in the modification of PLT activity by light.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular pathogenetic mechanism of peritonitis includes profound changes in blood plasma lipids [7]. Twenty-four hours after BP modeling the contents of cholesterol and β-lipoproteins increased to 4.42±0.22 mmol/liter (p<0.01) and 35.47±3.29 U (p<0.001), respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, R/NIR radiation causes biochemical changes in the membrane of PLTs in the lipid phase 35 , 40 , 41 . The authors suggest that the observed changes in the microviscosity of the lipid bilayer, also in the contact regions of lipids and proteins, may cause the activation of the cellular regulatory system and the synthesis of secondary messengers 40 . Such assumptions indicate that cell membrane structures contribute to the light modification of PLT activity.…”
Section: Discussionmentioning
confidence: 99%